Are the French happy with the 35-hour workweek? - Marcello Estev\~ao; Filipa Sá (Institute for the Study of Labor (IZA), 2006)
Legally mandated reductions in the workweek can be either a constraint on individuals' choice or a tool to coordinate individuals' preferences for lower work hours. We confront these two hypotheses by studying the consequences of the workweek reduction in France from 39 to 35 hours, which was first applied to large firms in 2000. Using the timing difference by firm size to set up a quasi-experiment and data from the French labor force survey, we show that the law constrained the choice of a significant number of individuals: dual-job holdings increased, some workers in large firms went to small firms where hours were not constrained, and others were replaced by cheaper, unemployed individuals as relative hourly wages increased in large firms. Employment of persons directly affected by the law declined, although the net effect on aggregate employment was not significant.
urn:nbn:de:101:1-20080702212
Keywords: 330